Sosialisasi dan Pendampingan Sertifikasi Halal Bagi Pelaku UMKM di Kabupaten Tanggamus Sebagai Upaya Penguatan Legalitas Produk - Ahmad, Azis (Universitas 17 Agustus 1945 Jakarta, 2025)
The low level of understanding and ability of UMKM actors regarding the halal certification process is an obstacle in fulfilling product legality obligations, especially in the food sector. This community service aims to increase the capacity of UMKM actors in the food sector in Tanggamus Regency in the halal certification process through a self-declare scheme. The activity was conducted in a hybrid format across four stages: preparation, socialization of SIHALAL regulations and technical aspects, assistance with document submission, and monitoring and evaluation of applications. The service providers accompanied 10 UMKM actors from account creation on SIHALAL, factual verification, to submission to the Halal Fatwa Committee. As a result, all participants successfully obtained official halal certificates from the BPJPH. This community service initiative also promoted improved digital literacy and compliance with halal regulations. The activity recommended strengthening collaboration between academics, SME operators, and stakeholders to accelerate halal certification and develop a competitive business ecosystem rooted in sharia values.